Edible Coating Formulated from Cocoa Pod Husk Pectin and Sungkai Leaf Extract to Extend Tomato Shelf Life - Humaira, H; Refilda; Yefrida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Tomato (Solanum lycopersicum L.) is a climacteric fruit that continues to ripen after harvest, leading to rapid spoilage and a short shelf life. This study investigated the use of cocoa pod husk pectin (Theobroma cacao L.) extracted via acid hydrolysis as a base material for edible coating, characterized by Fourier Transform Infrared (FTIR) spectroscopy. Various formulations were developed by combining cocoa pectin with sungkai leaf extract (Peronema canescens Jack) and compared to standard pectin (K, PC1–PC6). Physicochemical properties of tomatoes were analyzed over 15 days of storage (days 0, 3, 6, 9, 12, and 15), focusing on weight loss, decay rate, total soluble solids, titratable acidity, total antioxidant content, and total phenolic content. FTIR confirmed similar functional groups between cocoa pectin and standard pectin. Among the formulations, PC2 (pectin + aqueous sungkai extract) showed the best performance with 8.10% weight loss, 8.89% decay rate, 2.50° Brix, 0.36% titratable acidity, 0.65 mg AA/g FW antioxidant content, and 4.90 mg GAE/g FW phenolic content after 15 days at room temperature. Overall, cocoa pectin combined with sungkai leaf extract effectively maintained tomato quality and extended shelf life. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and ProductionSDG 2: Zero Hunger